The effect of single and dual antiplatelet therapy on the activity of pro-inflammatory cytokines in patients with coronary artery disease and obstructive sleep apnea - V. I. Ruzov; L. G. Komarova; A. S. Komarov; A. M. Vorobev; L. N. Savonenkova; O. V. Midlenko (Кардиоваскулярная терапия и профилактика)
Aim. To study the activity of pro-inflammatory cytokines in patients with coronary artery disease (CAD) associated with obstructive sleep apnea (OSA), depending on the type of antiplatelet therapy.Material and methods. The study included 148 patients with stable CAD, 30% (n=44) of whom had mild OSA, 10% (n=14) — moderate and severe OSA. There were 60% (n=90) of patients without OSA. Pro-inflammatory activity of cytokines was assessed by the level of interleukins (IL): IL- 1β, IL-6, IL-10.Results. Using dual antiplatelet therapy, there were no differences in aggregation activity of platelets (spontaneous and induced by 0,1 pM ADP) in patients with and without OSA. This indicates the synergism and potentiation of the antiplatelet effect of clopidogrel and acetylsalicylic acid (ASA). Patients with moderate and severe OSA and stable CAD had higher levels of IL- 1β and IL-6 compared with patients without OSA. Antiplatelet therapy, especially dual one, had an anti-inflammatory effect, which was reflected in lower values of pro-inflammatory IL both in patients with and without OSA.Conclusion. Patients with moderate and severe OSA and stable CAD had higher levels of pro-inflammatory IL (IL- 1β, IL-6) compared with patients without OSA. The combined use of clopidogrel and ASA potentiates antiplatelet and anti-inflammatory effects. This is reflected in lower values of pro-inflammatory IL and lower aggregation activity of platelets in patients with stable CAD, regardless of OSA.